2018
DOI: 10.1021/acs.macromol.8b01193
|View full text |Cite
|
Sign up to set email alerts
|

Blob Size Controls Diffusion of Free Polymer in a Chemically Identical Brush in Semidilute Solution

Abstract: The diffusion of rhodamine-labeled poly(ethylene glycol) (r-PEG) within surface-grafted poly(ethylene glycol) (s-PEG) layers in aqueous solution at 18 °C was measured by fluorescence correlation spectroscopy. The diffusion coefficient of r-PEG within s-PEG was controlled by the grafting density, σ, and scaled as σ–1.42±0.09. It is proposed that a characteristic blob size associated with the grafted (brush) layer defines the region through which the r-PEG diffusion occurs. The diffusion coefficients for r-PEG i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…50 That PEO takes up a pancake structure has been questioned for hydrophobic surfaces 51 but force spectroscopy has revealed that adsorption as a pancake does occurs on some surfaces. 23 Bulk measurements of PEO diffusion have a diffusion coefficient similar to the maximum surface diffusion values reported here, 22,26,28 and so it may be argued that the conformational transition just below the glass transition amounts to desorption. Nevertheless, the relative contributions of adsorption and desorption are important in some diffusion mechanisms.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…50 That PEO takes up a pancake structure has been questioned for hydrophobic surfaces 51 but force spectroscopy has revealed that adsorption as a pancake does occurs on some surfaces. 23 Bulk measurements of PEO diffusion have a diffusion coefficient similar to the maximum surface diffusion values reported here, 22,26,28 and so it may be argued that the conformational transition just below the glass transition amounts to desorption. Nevertheless, the relative contributions of adsorption and desorption are important in some diffusion mechanisms.…”
Section: Discussionsupporting
confidence: 79%
“…The maximum diffusion coefficients are similar to those in bulk solution for PEO of similar molar mass. 22,26,28 The blend data reveal two peaks in the diffusion coefficient: one corresponding to the glass transition temperature of the PBMA-rich phase and the other to that of the PMMA-rich phase. In both cases, the peaks are located ~10 K below the corresponding expansivity change measured using ellipsometry (Figure S1b).…”
Section: Friction Force Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The surface interactions acquired when the borosilicate colloidal probe was approaching the PIL samples were analyzed to validate the hypothesis that the PIL is solvated to lubricate in water, but is collapsed on the surface to form a compact layer in dodecane with minimal surface interaction. As demonstrated in previous studies, such a method offers both a qualitative judgment on the solvation state of the surface-grafted polymer and a quantitative approach to evaluate the thickness of the brush layer by measuring the onset of repulsion upon contact. ,, Figure shows representative plots of the approaching curves of all the PIL samples acquired in water and dodecane.…”
mentioning
confidence: 99%
“…As demonstrated in previous studies, such a method offers both a qualitative judgment on the solvation state of the surface-grafted polymer and a quantitative approach to evaluate the thickness of the brush layer by measuring the onset of repulsion upon contact. 16 , 45 , 51 54 Figure 6 shows representative plots of the approaching curves of all the PIL samples acquired in water and dodecane.…”
mentioning
confidence: 99%